Distributed multitarget tracking with range-doppler sensors - Battistelli, G.; Chisci, L.; Fantacci, Claudio; Farina, A.; Graziano, A. (IEEE, 2013)
The paper applies a recently developed Consensus Gaussian Mixture - Cardinalized Probability Hypothesis Density (CGM-CPHD) filter to distributed multitarget tracking with range and/or Doppler sensors. It is demonstrated via simulation results on realistic scenarios that the use of Doppler measurements provides a significant tracking performance improvement with respect to using low-accuracy range measurements only. On the other hand, effective distributed Doppler-only multitarget tracking is still an open issue to be investigated.